2019
DOI: 10.1016/j.ensm.2018.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical potassium/lithium-ion intercalation into TiSe2: Kinetics and mechanism

Abstract: As one promising candidate for next-generation energy storage systems, K-ion batteries (KIBs) attract increasing research attention due to the element abundance, low cost, and competent energy density as compared to Li-ion batteries. However, developing practical electrode materials in particular cathodes for KIBs is still in its infancy, and the related reaction mechanisms of the electrode materials are far from completely understood. In this work, TiSe2was, for the first time, investigated as an intercalated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(60 citation statements)
references
References 38 publications
1
58
1
Order By: Relevance
“…[ 26,32,33 ] In PIBs system, three cathodic peaks attributed to K + insertion are located at 2.20, 2.11, and 1.73 V, while three anodic peaks assigned to K + extraction are situated at 1.94, 2.32, and 2.91 V in the initial cycle (Figure 2c). [ 34 ] The discharge/charge curves of the VS 2 cathode consist of two discharge plateaus at 2.31 and 2.20 V, and four charge plateaus at around 2.23, 2.32, 2.41, and 2.48 V in LIBs (Figure 2d); two pairs of redox voltage plateaus at 2.11/1.63 and 2.30/1.90 V in SIBs (Figure 2e); two discharge voltage plateaus located at around 2.21 and 1.78 V and four charge voltage plateaus located at about 1.91, 2.47, 2.90, and 3.29 V in PIBs (Figure 2f). It is observed that the reduction and oxidation peaks in three battery systems shift after the first cycle.…”
Section: Resultsmentioning
confidence: 99%
“…[ 26,32,33 ] In PIBs system, three cathodic peaks attributed to K + insertion are located at 2.20, 2.11, and 1.73 V, while three anodic peaks assigned to K + extraction are situated at 1.94, 2.32, and 2.91 V in the initial cycle (Figure 2c). [ 34 ] The discharge/charge curves of the VS 2 cathode consist of two discharge plateaus at 2.31 and 2.20 V, and four charge plateaus at around 2.23, 2.32, 2.41, and 2.48 V in LIBs (Figure 2d); two pairs of redox voltage plateaus at 2.11/1.63 and 2.30/1.90 V in SIBs (Figure 2e); two discharge voltage plateaus located at around 2.21 and 1.78 V and four charge voltage plateaus located at about 1.91, 2.47, 2.90, and 3.29 V in PIBs (Figure 2f). It is observed that the reduction and oxidation peaks in three battery systems shift after the first cycle.…”
Section: Resultsmentioning
confidence: 99%
“…However, compared with Li + or Na + ions, K + ions (with an ionic radius of 1.4 Å) are much larger than Li + ions (0.76 Å) or Na + ions (1.02 Å), which induces sluggish potassiation kinetics and an inferior K + ion transfer and storage . So far, only a few binary TMDs cathode materials (i.e., TiS 2 , TiSe 2 ) and anode materials (i.e., VSe 2 , ReS 2 , MoS 2 , VS 2 , MoSe 2 ) for KIBs have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Up to date, the majority of TMDs research for KIBs has only focused on the design and preparation of binary layered 2D materials for achieving competitive electrochemical performances . For example, Loh and co‐workers reported that potassium‐intercalated TiS 2 (K x TiS 2 , 0 ≤ x ≤ 0.88) cathode materials could provide a reversible specific capacity of 145 mAh g −1 with a good stability after 120 cycles .…”
Section: Introductionmentioning
confidence: 99%
“…118 TiSe 2 was synthesized via a powder-sintering approach and the crystal structure is shown in Figure 7D. 73 Owing to the large interlayer space, TiSe 2 delivers an initial charge capacity of 92.7 mAh g −1 and maintains a reversible Reprinted with permission. 69 Copyright 2016, The Royal Society of Chemistry; E, F, Projections of the KTi 2 (PO 4 ) 3 structure along the 79 [100] and [001] directions respectively.…”
Section: Noncarbon-based Intercalation Anodesmentioning
confidence: 99%
“…Reprinted with permission. 73 Copyright 2018, Elsevier P carbon matrix (Co 3 O 4 -Fe 2 O 3 /C) was fabricated via the molten salt method, and here, the carbon matrix is able to enhance the conductivity as well as reduce the impact of volume change. 76 The electrochemical reaction process in the hybrid Co 3 O 4 -Fe 2 O 3 /C was proposed as follows: (a) Fe 2 O 3 + 6 K + + 6e − ⇌ 2Fe + 3K 2 O and (b) Co 3 O 4 + 8 K + + 8e − ⇌ 3Co + 4K 2 O.…”
Section: Conversion-type Anodesmentioning
confidence: 99%